T1 Relaxation Times in the Cortex and Thalamus Are Associated With Working Memory and Information Processing Speed in Patients With Multiple Sclerosis - Thaler, Christian; Hartramph, Isabelle; Stellmann, Jan-Patrick; Heesen, Christoph; Bester, Maxim; Fiehler, Jens; Gellißen, Susanne (Frontiers in Neurology, 2021)
Background Cortical and thalamic pathologies have been associated with cognitive impairment in MS patients. Objective We aimed to quantify cortical and thalamic damage in MS patients using a high resolution T1 mapping technique and to evaluate the association of these changes with clinical and cognitive impairment. Methods Forty-nine patients with mainly relapsing-remitting MS and 17 age-matched healthy controls received 3T MRI including a T1 mapping sequence (MP2RAGE). Mean T1 relaxation times (T1-RT) in the cortex and thalami were compared between MS patients and healthy controls. Additionally, correlation analysis was performed to assess the relation between MRI parameters and clinical and cognitive disability. Results MS patients had significantly decreased normalized brain, gray matter and white matter volumes as well as increased T1-RT in the normal-appearing white matter compared to healthy controls (p<0.001). Partial correlation analysis with age, sex and disease duration as covariates, revealed correlations for T1-RT in the cortex (r=-0.33, p<0.05), and thalami (right thalamus: r=-0.37, left thalamus: r=-0.50, both p<0.05) with working memory and information processing speed, as measured by the Symbol-Digit Modalities Test. Conclusion T1-RT in the cortex and thalamus correlate with information processing speed in MS patients.